Tinea capitis and tinea faciei in the Zurich area – an 8‐year survey of trends in the epidemiology and treatment patterns. (10th December 2014) - Kieliger, S.; Glatz, M.; Cozzio, A.; Bosshard, P.P.
Abstract Background Tinea capitis and tinea faciei are dermatophyte infections of the scalp and glabrous skin of the face affecting mainly prepubertal children. During the past 30 years, a significant increase and a change in the pattern of infectious agents has been noted for tinea capitis. Objectives The aim of this study was to determine trends in the current epidemiological situation of tinea capitis and tinea faciei in the Zurich area, Switzerland and adjacent Central and Eastern Switzerland. Methods Consecutive cases diagnosed between 2006 and 2013 were studied retrospectively. Results A total of 90 tinea capitis and 40 tinea faciei cases were observed. Anthropophilic isolates (primarily Trichophyton violaceum and Microsporum audouinii) accounted for 76% of tinea capitis cases. In contrast, zoophilic isolates (primarily T. interdigitale) were responsible for 73% of tinea faciei cases. The peak incidence in both conditions was in 4–8 year‐old children. While the annual number of tinea faciei cases remained stable over the past 8 years, a trend for an increase in T. violaceum‐positive tinea capitis has been observed. This was mainly due to patients of African ethnicity. Conclusions Anthropophilic isolates accounted for three quarters of tinea capitis and one quarter of tinea faciei cases. T. violaceum‐positive tinea capitis was primarily linked to patients of African ethnicity. Tinea capitis caused by Microsporum spp. was more refractory to therapy and needed longer treatment than Trichophyton spp.‐induced infection.